Biologia floral e reprodutiva de Petunia interior T. Ando & Hashim (SOLANACEAE) - Souza, Suzana dos Santos de (2020)
The genus Petunia Juss is represented by herbaceous species characterized mainly by having hermaphrodite flowers with different colors (white, red and purple tones) and interactions with different groups of pollinators (hawkmoths, hummingbirds and bees). Considering the existence of specialized interactions between Petunia species and oligolectic bees, and that the survival of these insects depends on the conservation of their favorite plants, we highlight the need to know and disseminate information about the floral and reproductive biology of Petunia interior, a species, whose flowers are pollinated by bees. The study was conducted at the Experimental Station of the Federal University of Southern Frontier, (28°08'29.5"S; 54°45'42.2"W), Cerro Largo, Rio Grande do Sul, Brazil, where natural populations of P. interior occur. Were investigated: floral morphology (measurements of floral whorls, number of ovules and pollen grains/flower, and substances present in the anther's locular fluid), floral biology (number of flowers opened per hour, floral longevity, dehiscence period of the anthers, receptivity of stigma, spontaneous self-deposition of pollen on the stigma, volume and concentration of nectar) and reproductive biology (modes of reproduction through pollination experiments, and reproductive success through the analysis of fruit variables). The flowers of P. interior are purple and the pollen is violet and covered with pollenkitt. In addition, they have a wide and short floral tube that keeps heterodynamic stamens and stigma included, which despite being close to each other rarely resulted in self-pollination. The opening and senescence of the flowers occurred asynchronously and the plants maintained a floral display of 16,8 flowers/individual. The flowers showed a long period of stigmatic receptivity, gradual dehiscence of the anthers and continuous release of low volumes of nectar. Regarding the reproductive system, despite the registration of set fruit by autogamy (10%), the ISI of 0.9 classified the species as obligatory xenogamous. Thus, given the absence of pollination deficit and the equivalent quality of the fruits formed in the treatment of cross-pollination and control pollination, we conclude that the floral characteristics of P. interior were essential to ensure the attractiveness and consequent efficiency of the pollinators in the reproduction of this species. Finally, we emphasize that this study was of fundamental importance to understand the biology of P. interior, which, due to its interactions with specialized bees, should be the target of preservation in its natural environments.